“Blessed are the Peacemakers”: John Donne and Péter Pázmány on Religious Tolerance - Najbauer, Noémi Mária (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Those familiar with the Bible will recognize the first half of the title as a quotation from the Sermon on the Mount in the Gospel of Matthew. It is part of the Eight Beatitudes, which constitute the core of Christian moral teaching. The full beatitude reads, “Blessed are the peacemakers, for they shall be called the children of God” (Matthew 5:9). I would like to treat religious tolerance and interdenominational peace as dreamed by two seventeenth-century churchmen, hence the pertinence of the Biblical citation. These same words, “Blessed are the peacemakers,” echo the Latin motto, Beati pacifici, of James I of England and VI of Scotland, the Stuart monarch committed to peace in Christendom (Stubbs 337). By quoting the motto of this pacifist king, I wish to refer to a specific peacemaking attempt, which took the form of a diplomatic mission to the Holy Roman Emperor Ferdinand II. The irenic English statesmen, with Donne as their chaplain, arrived in Vienna in the October of 1619 with the unfortunately futile mission of preventing, or at least nipping in the bud, what was to become the Thirty Years’ War. And it is during this failed peace mission that Donne may have met Péter Pázmány.